Tumour-secreted miR-9 promotes endothelial cell migration and angiogenesis by activating the JAK-STAT pathway - Zhuang, Guanglei; Wu, Xiumin; Jiang, Zhaoshi; Kasman, Ian; Yao, Jenny; Guan, Yinghui; Oeh, Jason; Modrusan, Zora; Bais, Carlos; Sampath, Deepak; Ferrara, Napoleone (The EMBO journal, 2012)
Angiogenesis plays a crucial role during tumorigenesis and much progress has been recently made in elucidating the role of VEGF and other growth factors in the regulation of angiogenesis. Recently, microRNAs (miRNAs) have been shown to modulate a variety of physiogical and pathological processes. We identified a set of differentially expressed miRNAs in microvascular endothelial cells co‐cultured with tumour cells. Unexpectedly, most miRNAs were derived from tumour cells, packaged into microvesicles (MVs), and then directly delivered to endothelial cells. Among these miRNAs, we focused on miR‐9 due to the strong morphological changes induced in cultured endothelial cells. We found that exogenous miR‐9 effectively reduced SOCS5 levels, leading to activated JAK‐STAT pathway. This signalling cascade promoted endothelial cell migration and tumour angiogenesis. Remarkably, administration of anti‐miR‐9 or JAK inhibitors suppressed MV‐induced cell migration in vitro and decreased tumour burden in vivo . Collectively, these observations suggest that tumour‐secreted miRNAs participate in intercellular communication and function as a novel pro‐angiogenic mechanism. Secreted miRNAs are increasingly recognized in multiple biological processes. Here, miR‐9 is shown to be secreted from cancer cells to enhance endothelial recruitment. This contribution to tumour angiogenesis could be amenable for therapeutic intervention.